The effectiveness and safety of palbociclib and ribociclib in stage IV HR+/HER-2 negative breast cancer: a nationwide real world comparative retrospective cohort study - Al-Ziftawi, Nour Hisham; Elazzazy, Shereen; Alam, Mohammed Fasihul; Shafie, Asrul; Hamad, Anas; Bbujassoum, Salha; Mohamed Ibrahim, Mohamed Izham (Frontiers in Oncology, 2023)
Introduction Palbociclib and ribociclib are indicated in the first-line treatment of hormonal receptor-positive HER-2 negative (HR+/HER2- negative) advanced breast cancer. Although randomized-controlled trials (RCTs) proved their clinical efficacy, there are no observational studies yet to validate the clinical findings in the real-world. Therefore, this study aimed to evaluate and compare the clinical effectiveness and safety profiles of palbociclib and ribociclib in Qatar. Materials and methods A retrospective observational study was conducted on HR+/HER-2-negative stage-IV breast cancer patients receiving palbociclib or ribociclib in the state of Qatar. Clinical data were collected from the National Center for Cancer Care and Research (NCCCR) in Qatar using Cerner®. Primary outcomes were progression-free-survival (PFS) and overall-survival (OS) generated by Kaplan-Meier curves. Moreover, safety profiles of both two treatments were evaluated. Results The data from 108 patients were included in the final analysis. There was no statistically significant difference in PFS between the palbociclib and ribociclib groups; PFS was 17.85 versus 13.55 months, respectively(p> 0.05). Similarly, there was no statistically significant difference in OS between the two medications, 29.82 versus 31.72 months, respectively(p>0.05). Adverse events were similar between the two groups. Neutropenia was the most common side effect in the study population accounting for 59.3% of the patients. Conclusions Therefore, both treatments have similar efficacy and safety profiles. Further research on a larger-scale population and longer follow-up period is recommeneded.